2020
DOI: 10.3390/ijms21072576
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Exocytosis, Exosome Release and Secretory Autophagy: The Autophagic- and Endo-Lysosomal Systems Go Extracellular

Abstract: Beyond the consolidated role in degrading and recycling cellular waste, the autophagic-and endo-lysosomal systems play a crucial role in extracellular release pathways. Lysosomal exocytosis is a process leading to the secretion of lysosomal content upon lysosome fusion with plasma membrane and is an important mechanism of cellular clearance, necessary to maintain cell fitness. Exosomes are a class of extracellular vesicles originating from the inward budding of the membrane of late endosomes, which may not fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
204
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 154 publications
(198 reference statements)
1
204
0
Order By: Relevance
“…The late endosomes/MVB can fuse with plasma membranes or with lysosomes where their content is degraded becoming available for the cell again [ 14 ]. Recent studies also demonstrate that exosomes can be present in lysosomes where they are not degraded but released by lysosomal exocytosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The late endosomes/MVB can fuse with plasma membranes or with lysosomes where their content is degraded becoming available for the cell again [ 14 ]. Recent studies also demonstrate that exosomes can be present in lysosomes where they are not degraded but released by lysosomal exocytosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the virus attack destroys the host cell machinery leading to the release of lysosomes: this disruption of cell integrity results in cell death and consequent release of virus particles. [ 80 , 81 ] Finally, these progeny virions get released out of the host cell in vesicles by exocytosis. These newly released virions may either infect other healthy cells or shed into the environment via the opening of the mouth, breathing, or similar occurrences that may infect healthy persons via reported modes of transmission.…”
Section: Sars-cov-2 Entry and Initiationmentioning
confidence: 99%
“…Sato et al (2019) reported that rapamycin, a known activator of macroautophagy, stimulated microautophagy in cells by TFEB stimulation and hypothesized its involvement in neurodegenerative diseases. The delivery of proteins to be degraded within vesicles resembled a "secretory autophagy" mechanism and intraluminal exosomes formation (Buratta et al, 2020).…”
Section: Microautophagymentioning
confidence: 99%